Marxist Perspective In “Caged Bird” By Maya Angelou - I Made Satria Bayu Temaja; Novita Mulyana; I Nyoman Tri Ediwan; Gek Wulan Novi Utami (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Literature and social life have a close relationship. Many writers express ambiguous emotions when observing their surroundings. Society is a mixture of the upper and lower classes. Due to the imbalance of wealth, the lower classes often experience different fates in life, while the upper classes enjoy the benefits. Karl Marx has pointed out this social injustice in his theory. This research is an attempts to find elements of Marxism related to social inequalities in the poem "Caged Bird" by Maya Angelou. This study uses the text analysis method through the lens of Karl Marx's propositions about the behavior of the lower or marginalized social class in facing the severity of life. This research is a qualitative research that uses descriptive text analysis methods to explore the social and economic dimensions hidden in the text. In this study, Using a Marxist approach, this research seeks to uncover the layers of meaning contained in each line of the poem, highlighting the sharp contrast between the upper class and the marginalized class. Thus, this view states that how economic forces create inequalities and make life difficult for the lower classes. The poem challenges readers to consider the impact